Gendered livelihood implications for improvements of livestock water productivity in Zimbabwe - Senda, Trinity S.; Peden, Donald G.; Homann-Kee Tui, Sabine; Sisito, G.; Rooyen, Andre F. van; Sikosana, J.L.N. (Cambridge University Press, 2011)
Scarcity, lack of access, and ineffective and inefficient use of water in Nkayi District, Zimbabwe, threaten agricultural production. The purpose of this study is to augment understanding of opportunities to increase livestock water productivity (LWP) in Nkayi District by taking into account key differences in the capacities, opportunities, and needs of women and men. There are two important types of female-headed households, de facto and de jure. The results from this study showed thatmale-headed and de facto and de jure female-headed households sharemuch in common.They all had similar areas of cropland and access to education, finances, veterinary and extension services, and transportation and markets. Households of all types had similar herd sizes. All were desperately poor with incomes much less than a dollar a day. To rise out of poverty, the knowledge, skills and effort of all household heads will be needed. In spite of severe poverty, household heads of all types are literate and have sufficient education that can help enable adoption of intervention options that can lead to increased agricultural production and improved livelihoods. The results also showed that major differences exist in terms of the roles of men and women in ownership, management and decision making related to livestock keeping and animal production. Men clearly dominate in both ownership and decision making even though women play a major role in animal management. Only in de jure female-headed households were womenmore likely thanmen to own cattle and goats. They were also more likely to be involved in farming as a primary livelihood activity. Surprisingly, men were more likely to be involved in animal management in these de jure female-headed households. Women were also excluded from water users’ and livestock producers’ associations although a minority of men was members. By not involving the already-developed capacity of women, the community loses out on a significant opportunity to increase LWP and animal production more widely. Greater inclusion of women in decision making will be an important part of future efforts to improve livelihoods through livestock development.